Aqidah Teachers' Strategies in Instilling Religious Values: A Case Study of Grade VII Students of the As-Syahaadah Pakpak Bharat Islamic Boarding School - Azizah Nurfatimah Cibro (EDUJAVARE: International Journal of Educational Research, 2024)
This study examines the strategy of Aqidah teachers in instilling religious values in grade VII students at the As-Syahaadah Islamic Boarding School, Pakpak Bharat. Using a qualitative approach with a case study method, this research involves in-depth interviews, classroom observations, and document analysis. The study results show that the main strategies used include worship habituation, contextual approaches, and dialogical methods. The positive impact can be seen from the increase in students' understanding of religious values, with the average score increasing from 70% to 85%. Positive changes in attitudes and behaviors were also observed, including increased respect for teachers and active participation in worship activities. Despite this, challenges such as the diversity of students' backgrounds and limited resources are still faced. This study recommends increasing teacher training, curriculum development, and improving facilities to support the effectiveness of instilling religious values in Islamic boarding schools.